The global economic crisis and consequences for development strategy in Dubai - Al Sadik, Ali Tawfik; Elbadawi, Ibrahim (Palgrave Macmillan, 2012)
This book identifies and addresses the impacts of the global financial crisis on Dubai and the region. The issues are highlighted and analyzed by a group of distinguished scholars. Specifically, discussions are focused on the following four interrelated issues: Why and how the financial crisis happened and what are its consequences for the economies of the Middle East? Defining the emerging global regulatory framework and the new financial architecture; The long term development strategy for the UAE / Dubai in the post crisis global economy; and The oil market and the global financial crisis
Keywords: Spatial economics; Economics; Economic theory; Macroeconomics; Development economics; Economic growth; Regional economics